Community networks and the growth of private enterprise in China - Dai, Ruochen; Mookherjee, Dilip; Munshi, Kaivan; Zhang, Xiaobo (2018)
Social networks substituted for legally enforced contracts between firms and paved the way for entrepreneurs to flourish.